2020 IEEE Conference on Virtual Reality and 3D User Interfaces (VR) 2020
DOI: 10.1109/vr46266.2020.00034
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Planning for Redirected Walking Based on Reinforcement Learning in Multi-user Environment with Irregularly Shaped Physical Space

Abstract: Fig. 1: Reset control during multi-user RDW experience in a physical space with a circle obstacle in the center: (a) Reset-to-Center (R2C): the user unconditionally reset to the center of the physical space without considering other users or obstacle in the center. (b) Reset-to-Gradient (R2G): the user reset to the direction of the sum of the force that is acted on them by the boundary of the physical space, obstacles, and other users. (c) Multi-user Reset Controller (MRC): the user reset to the optimal direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 40 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…Dong et al [16] introduced Smooth Assembly Mapping (SAM), which decomposes large VE to smaller local patches and mapping together into a real workspace. For multi-user scenarios, Azmandian et al [4] explored immersive VR experiences for redirected walking for two users in the same physically tracked space, and Lee et al [27] used reinforcement learning in a multi-user environment with heterogeneous physical space.…”
Section: Redirected Walking Techniquesmentioning
confidence: 99%
“…Dong et al [16] introduced Smooth Assembly Mapping (SAM), which decomposes large VE to smaller local patches and mapping together into a real workspace. For multi-user scenarios, Azmandian et al [4] explored immersive VR experiences for redirected walking for two users in the same physically tracked space, and Lee et al [27] used reinforcement learning in a multi-user environment with heterogeneous physical space.…”
Section: Redirected Walking Techniquesmentioning
confidence: 99%
“…Moreover, non-convex PEs like the cross and L-shaped rooms lead to more collisions than the convex PEs. Lee et al [22] also studied how RDW algorithms perform as the shape and size of the PE changes. In their work, they considered square PEs of varied sizes, as well as PEs in the shape of a square, trapezoid, cross, circle, T, and L, each with a roughly equal area.…”
Section: Locomotion In Virtual Environmentsmentioning
confidence: 99%
“…In their work, they considered square PEs of varied sizes, as well as PEs in the shape of a square, trapezoid, cross, circle, T, and L, each with a roughly equal area. Lee et al [22] observed that larger PEs lead to fewer collisions and that non-convex PE shapes like cross, T, and L lead to more collisions than the convex PEs. Williams et al [43] introduced the Complexity Ratio (CR) metric to quantify the navigability of a PE, VE pair.…”
Section: Locomotion In Virtual Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, simulations have been performed to compare different redirection strategies [19], design new redirection methods [5,43], optimize obstacle avoidance in constrained workspaces [42,48], study the size and shape of the workspace [3,24], or minimize collisions between several redirected users in the same workspace [4,5,23]. Where most implementations of redirection techniques rely on human-engineered logic, it is worth noting that recent work showed that machine-learning with simulation approaches could outperform the state of the art steering algorithms used for redirected walking [23,36,41].…”
Section: Redirected Walking and Simulation Based Evaluationsmentioning
confidence: 99%